Pistil Transcriptome Analysis to Disclose Genes and Gene Products Related to Aposporous Apomixis in Hypericum perforatum L. - Galla, Giulio; Zenoni, Sara; Avesani, Linda; Altschmied, Lothar; Rizzo, Paride; Sharbel, Timothy F.; Barcaccia, Gianni (Frontiers in Plant Science, 2017)
Unlike sexual reproduction, apomixis encompasses a number of reproductive strategies, which permit maternal genome inheritance without genetic recombination and syngamy. The key biological features of apomixis are the circumvention of meiosis (i.e., apomeiosis), the differentiation of unreduced embryo sacs and egg cells, and their autonomous development in functional embryos through parthenogenesis, and the formation of viable endosperm either via fertilization-independent means or following fertilization with a sperm cell. Despite the importance of apomixis for breeding of crop plants and although much research has been conducted to study this process, the genetic control of apomixis is still not well understood. Hypericum perforatum is becoming an attractive model system for the study of aposporous apomixis. Here we report results from a global gene expression analysis of H. perforatum pistils collected from sexual and aposporous plant accessions for the purpose of identifying genes, biological processes and molecular functions associated with the aposporous apomixis pathway. Across two developmental stages corresponding to the expression of aposporous apomeiosis and parthenogenesis in ovules, a total of 224 and 973 unigenes were found to be significantly up- and down-regulated with a fold change ≥ 2 in at least one comparison, respectively. Differentially expressed genes were enriched for multiple gene ontology (GO) terms, including cell cycle, DNA metabolic process, and single-organism cellular process. For molecular functions, the highest scores were recorded for GO terms associated with DNA binding, DNA (cytosine-5-)-methyltransferase activity and heterocyclic compound binding. As deregulation of single components of the sexual developmental pathway is believed to be a trigger of the apomictic reproductive program, all genes involved in sporogenesis, gametogenesis and response to hormonal stimuli were analysed in great detail. Overall, our data suggest that phenotypic expression of apospory is concomitant with the modulation of key genes involved in the sexual reproductive pathway. Furthermore, based on gene annotation and co-expression, we underline a putative role of hormones and key actors playing in the RNA dependent DNA methylation pathway in regulating the developmental changes occurring during aposporous apomixis in H. perforatum.